Certain vacuum Bianchi-type models in a new relativistic theory of gravitation - Singh T.; Agrawal A.K. (My University, 2025)
The vacuum Bianchi type-I, III, V, VI0 and Kantowski-Sachs models have been obtained in a new scalar-tensor theory formulated by Lau and Prokhovnik (1986) under the assumption of a certain relationship between the cosmological term Λ and the scalar field ψ. The dynamical behaviour of these models have been studied. © 1991 Kluwer Academic Publishers.